The Effect of Work Life Balance on Motivation in Implementing WFH Policies during the COVID-19 Pandemic - et. al., Nabilah Ramadhan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the effect of work life balance on employee motivation during the implementation of WFH policies in dealing with the COVID-19 pandemic. Descriptive research method was used to get informations of the quality work life balance and motivation. Causal research method was used to know how the influence of work life balance on motivation. Survey questionnaire was used to collect the datas from 69 employee of a telecommunications company in Bandung. The results showed that the work life balance and work motivation of the employees were in the high category even in a pandemic condition. By using multiple regression analysis, the result revealed that work life balance has significant positive influence on motivation by 37,4%.